Students‘ attitudes in the perception of broadcast advertising meanings - Ekaterina E. Belousova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The aim of the research presented in the paper is the empirical study of the semantic attitudes and life meanings of students in the perception of advertising posters. Advertising impact is viewed as a process of broadcasting the meanings concentrated in advertising posters. The study sample consisted of 80 students from two universities (Rostov-on-Don, Russia). To determine the severity of life meanings, the method of life meanings was used by V.Yu. Kotlyakov (V.Yu. Kotlyakov, 2003), the method of expert assessments was used to study advertising posters. The results were processed using the methods of mathematical statistics: descriptive statistics were used; as well as nonparametric tests for comparing several independent samples, the Kruskal-Wallis H-test, for studying the relationships between the scales of V.Yu. Kotlyakov and the assessment of advertising posters by the respondents used the Spearmans rank correlation coefficient. It was shown that in the process of broadcasting meanings in advertising posters, students semantic attitudes are actualized. The sample of students showed a tendency to evaluate advertising posters in accordance with the dominant meanings of life. It is shown that there is a relationship between the dominant life meanings of students and the ratings of advertising posters.